ECT-induced primary open-angle glaucoma in a patient with unstable thyroid function: a case report - Fu, Cuiyuan; Yang, Xiuzhen; Li, Kun (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia is a prevalent and severe psychiatric disorder for which electroconvulsive therapy (ECT) is frequently utilized as a treatment modality. Although ECT can transiently elevate intraocular pressure, the incidence of ECT-related adverse ophthalmic events in patients with coexisting hyperthyroidism is not well documented.Case reportIn this report, we describe an elderly woman with schizophrenia and hyperthyroidism. Before undergoing ECT, she had no previous history of glaucoma, and her thyroid function was in an unstable state. After three sessions of ECT, the patient exhibited conjunctival congestion and was subsequently diagnosed with primary open-angle glaucoma, which was not treated. Her intraocular pressure normalized prior to and following the fourth ECT session, and she experienced no further ocular discomfort during subsequent treatments (fifth through eighth sessions).ConclusionsAlthough ECT has been used in patients with coexisting psychiatric and thyroid dysfunction, there is a lack of reports addressing the risk of inducing or exacerbating glaucoma in the context of unstable thyroid function. This case emphasizes the necessity of monitoring intraocular pressure in patients with unstable thyroid function during ECT, to mitigate the risk of ocular complications.